2003
DOI: 10.1239/jap/1044476835
|View full text |Cite
|
Sign up to set email alerts
|

On the integral of the workload process of the single server queue

Abstract: This paper is devoted to a study of the integral of the workload process of the single server queue, in particular during one busy period. Firstly, we find asymptotics of the area 𝒜 swept under the workload process W(t) during the busy period when the service time distribution has a regularly varying tail. We also investigate the case of a light-tailed service time distribution. Secondly, we consider the problem of obtaining an explicit expression for the distribution of 𝒜. In the general GI/G/1 case, we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Another application area is statistical physics, see, e.g., [8] or [3] and references therein. Applications to queuing theory for the analysis of the load in Transmission Control Protocol networks and to risk theory are discussed in [2].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another application area is statistical physics, see, e.g., [8] or [3] and references therein. Applications to queuing theory for the analysis of the load in Transmission Control Protocol networks and to risk theory are discussed in [2].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…In the light-tailed case logarithmic asymptotics for P(A τ > x) was obtained in [10], and exact local asymptotics in [14]. Heavy-tailed asymptotics for P(A τ > x) was previously studied in [2], which considered the case when the increments of the random walk have a distribution with regularly varying tail, that is F(x) = x −α L(x), where L(x) is a slowly varying function. For α > 1 it was shown that…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also reveal a lacuna in [3,Theorem 4.1] where the most likely path is assumed to be piecewise linear.…”
mentioning
confidence: 99%